Model Mediasi Surplus Underwriting pada Pengaruh Pendapatan dan Biaya terhadap Laba Asuransi Syariah - Supriyadi, Teguh; Soeharjoto, Soeharjoto (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effect of Contribution Income, Claim Expenses, and Operating Expenses on Islamic Insurance Profit, with Underwriting Surplus as a mediating variable. This research is motivated by the importance of financial performance and risk management in improving the profitability of Islamic insurance companies. Therefore, this study is conducted to examine both the direct and indirect effects among variables and to assess the role of underwriting surplus in shaping Islamic insurance profits. The research method employed is a quantitative approach using Structural Equation Modeling–Partial Least Square (SEM-PLS) analysis with the SmartPLS 4 application. The data used are secondary data obtained from the annual financial statements of Islamic insurance companies in Indonesia during the research period. The research variables include Contribution Income, Claim Expenses, and Operating Expenses as independent variables, Islamic Insurance Profit as the dependent variable, and Underwriting Surplus as the mediating variable. Model testing is carried out through the evaluation of path coefficients and R-square values to assess the simultaneous contribution of the variables. The results indicate that Contribution Income and Operating Expenses do not have a significant effect on Underwriting Surplus, while Claim Expenses have a positive and significant effect on Underwriting Surplus. Furthermore, with respect to Islamic Insurance Profit, Contribution Income and Claim Expenses have a positive and significant effect, whereas Operating Expenses and Underwriting Surplus do not have a significant effect. In addition, the mediation test results show that Underwriting Surplus does not play a significant mediating role in the relationship between Contribution Income, Claim Expenses, and Operating Expenses on Islamic Insurance Profit. These findings suggest that the profits of Islamic insurance companies are more directly influenced by contribution income and effective claim management.